Peran Perempuan Dalam Transformasi Manajemen Sumber Daya Insani - Muhammad Afiqul Rifqi; Hikmatus Sa’diyah; Sifwatir Rif'ah (EQUALITY: Journal of Gender, Child, and Humanity Studies, 2024)
This study aims to analyze the strategic role of women in the transformation of Human Resource Management (HRM), particularly in creating inclusive, adaptive, and innovative work environments. HRM transformation demands a human- and technology-based approach, where women play a significant role in inclusive policies, strategic decision-making, training, and digital transformation.The research employs a library research method, utilizing data from journal articles, books, industry reports, and academic publications related to HRM and gender equality.The results indicate that women have unique abilities in collaboration, empathy, and innovation. They are capable of promoting balanced work-life policies and effectively leading digital transformations, making them strategic assets in sustainable HRM management.